High-Intensity Acute Exercise and Directed Forgetting on Memory Function - Mary Elizabeth Pace; Paul D. Loprinzi (Medicina, 2019)
Background and Objectives: Despite accumulating research demonstrating that acute exercise may enhance memory function, very little research has evaluated whether acute exercise can effectuate intentional directed forgetting (DF), an adaptative strategy to facilitate subsequent memory performance. Materials and Methods: A three-arm parallel-group randomized controlled intervention was employed. Participants were randomized into one of three groups, including: (1) exercise plus DF (Ex + DF), (2) DF (directed forgetting) only (DF) and (3) R (remember) only (R). The acute bout of exercise included 15 min of high-intensity treadmill exercise. The memory assessment involved the presentation of two-word lists. After encoding the first word list, participants were either instructed to forget all of those words (DF) or to remember them. Following this, participants encoded the second word list. Results: We observed a statistically significant main effect for list F(1, 57) = 12.27, p < 0.001, η2p = 0.18, but no main effect for group F(2, 57) = 1.32, p = 0.27, η2p = 0.04, or list by group interaction, F(2, 57) = 2.89, p = 0.06, η2p = 0.09. Conclusions: This study demonstrates a directed forgetting effect in that cueing an individual to forget a previously encoded list of items facilitates memory performance on a subsequent list of items. However, we failed to demonstrate any beneficial effect of acute exercise in facilitating directed forgetting. These findings are discussed in the context of directed forgetting theories, particularly the attention inhibition mechanism, as well as the timing of the acute bout of exercise.